Basic constitutional conceptions in the countries of former Yugoslavia: A comparative analysis - Đukanović Dragan (Međunarodni Problemi)
This article focuses on the constitutional framework of the states established within the borders of the former SFR of Yugoslavia. The author analyses particularly the following issues: constitutional definitions of the states, human rights regulation, organization of the governance organization of the states, status of the local government and constitutional protection of the ethnic minorities rights.